Socialization and Making Briquettes from Rice Husk Waste and Tapioca Flour in Braja Indah Village, Braja Selebah Subdistrict, East Lampung Regency - Sahyani, Aditya Anugrah; Rifqi, Muhammad Fakhri; Putri Ilda Damayanti; Nurjanah, Umi Anisa; Dewi, Soraya Tiana; Prastika, Myshel Wihasna; Prastika, Casrini (Indonesian Journal of Community Services Cel, 2024)
Briquettes are solid fuels made from waste materials. Rice husks serve as the primary raw material for briquette production. This article provides an overview of a training program aimed at introducing the production of briquettes from rice husks and tapioca flour in Braja Indah Village. The program was carried out in three stages: the survey process, product preparation, and training activities. This article adopts a qualitative approach with a descriptive-explanatory model. The outcome of the program was the production of briquettes capable of igniting successfully. Through this training, the community gained new insights and information on managing rice husk waste into more beneficial products, thereby reducing rice husk waste that could otherwise contribute to environmental pollution. This initiative was a collaborative effort between university students participating in community service (KKN) and the local government of Braja Indah Village to promote the program.